2018
DOI: 10.1123/jsr.2016-0164
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Functional Movement Retraining to Improve Pain, Function, and Biomechanics in Subjects With Anterior Knee Pain: A Case Series

Abstract: A subject-specific functional movement retraining intervention may be successful in the treatment of subjects with AKP presenting with biomechanical risk factors. Research on a larger sample is required to further investigate this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Our initial assessment level of function for the low back and lower extremity injuries were similar to baseline level of function in other studies (Oswestry 75.6±12.4%, compared to another study (70-80%) 24 , and LEFS 61.5%±22.9 compared with other studies examining patella femoral pain syndrome or anterior knee pain (61-75%). 27,28 ) However our mean DASH score (74.2±20.8%) was a generally higher compared to other studies. For example, the DASH score for other conditions include: hand, elbow and shoulder pathologies (65%) 33 , carpal tunnel syndrome (59%±20) 33 and rotator cuff tendinopathy (43.7%).…”
Section: Baseline Level Of Functioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Our initial assessment level of function for the low back and lower extremity injuries were similar to baseline level of function in other studies (Oswestry 75.6±12.4%, compared to another study (70-80%) 24 , and LEFS 61.5%±22.9 compared with other studies examining patella femoral pain syndrome or anterior knee pain (61-75%). 27,28 ) However our mean DASH score (74.2±20.8%) was a generally higher compared to other studies. For example, the DASH score for other conditions include: hand, elbow and shoulder pathologies (65%) 33 , carpal tunnel syndrome (59%±20) 33 and rotator cuff tendinopathy (43.7%).…”
Section: Baseline Level Of Functioncontrasting
confidence: 81%
“…The minimal clinically important difference is 9 points 26 , also equivalent to 11.25%. The Lower Extremity Functional Scale also demonstrates good construct validity (correlations with another scale ranging from 0.8 to 0.64 26 ) and reliability (test re-test r score ranging between 0.94 and 0.98) and is responsive for use in patients with lower extremity musculoskeletal dysfunction that include anterior knee pain 27 , patello-femoral pain syndrome. 28 Moreover, LEFS was the most used PROM for hip and knee dysfunctions 4 .…”
Section: Lower Extremity Functional Scale (Lefs)mentioning
confidence: 99%
See 1 more Smart Citation
“…This instrument has been used to assess a participant’s initial function as well as ongoing response to treatment for lower extremity pain (Binkley et al 1999 ; Lieberz et al 2022 ; Mehta et al 2016 ). The LEFS has been reported to have strong construct validity and test–retest reliability (Binkley et al 1999 ) and has been reported to be appropriate for use in individuals with lower extremity musculoskeletal dysfunction and pain (Binkley et al 1999 ; Fukuda et al 2010 ; Leibbrandt and Louw 2018 ). The scale is composed of 20 items that are evaluated on a Likert scale (0 = extreme difficulty; 4 = no difficulty) across many activities of daily living.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of the individually tailored exercises over the 6-week period can be seen as supplementary online data. The therapist’s instructions to the patient as well as criteria for progression has been described in detail in a previous study26 ) .…”
Section: Participants and Methodsmentioning
confidence: 99%